Gender-based reciprocal expression of transforming growth factor-β1 and the inducible nitric oxide synthase in a rat model of cyclophosphamide-induced cystitis - Loughran Patricia A; Barclay Derek; Witteemer Erich; Yoshimura Naoki; Tyagi Vikas; Tyagi Pradeep; Zamora Ruben; Vodovotz Yoram (BMC, 2009)
Abstract Background The pluripotent cytokine transforming growth factor-β1 (TGF-β1) is the central regulator of inducible Nitric Oxide Synthase (iNOS) that is responsible for nitric oxide (NO) production in inflammatory settings. Previous studies have implicated a role for NO, presumably derived from iNOS, in cyclophosphamide (CYP)-induced cystitis in the bladder. TGF-β1 is produced in latent form and requires dissociation from the latency-associated peptide (LAP) to act as primary anti-inflammatory and pro-healing modulator following tissue injury in the upper urinary tract. Since the role of TGF-β1 in lower urinary tract inflammation is currently unknown, and since gender-based differences exist in the setting of interstitial cystitis (IC), the present study examined the relationship between TGF-β1 and iNOS/NO in the pathogenesis of CYP-induced cystitis in both male and female rats. Methods Sprague-Dawley rats, 4 months of age, of either gender were given 150 mg/kg CYP intraperitoneally. Urinary and bladder tissue TGF-β1 and NO reaction products (NO2-/NO3-) were quantified as a function of time following CYP. Expression of active and latent TGF-β1 as well as iNOS in harvested bladder tissue was assessed by immunohistochemistry. Results Female rats had significantly higher levels of NO2-/NO3- in urine even at baseline as compared to male rats (p < 0.001), whereas there was no gender based significant difference in urine levels of active or latent TGF-β1 prior to CYP injection. Inflammatory and cytotoxic changes were induced by CYP in the bladder of both sexes that were accompanied by differences in the urine levels of NO2-/NO3- and TGF-β1. Male rats responded to CYP with significantly lower levels of NO2-/NO3- and significantly higher levels of TGF-β1 in urine (p < 0.05) as compared to females at all time points after CYP. The urine levels of NO2-/NO3- after CYP were inversely correlated to latent and active TGF-β1 (Pearson coefficient of -0.72 and -0.69 in females and -0.89 and -0.76 in males, respectively; p < 0.01). Bladder tissue of male rats exhibited significantly higher levels of both latent and active TGF-β1 (p < 0.01) compared to female rats after CYP. TGF-β1 and iNOS protein was mostly localized in the urothelium. Conclusion The results of this study suggest that there exists an inverse relationship between the expression of TGF-β1 and iNOS/NO2-/NO3- in CYP-inflamed bladder. The gender of the animal appears to magnify the differences in urine levels of TGF-β1 and NO2-/NO3- in this inflammatory setting. These results support the hypothesis that TGF-β1 can suppress iNOS expression associated with bladder inflammation and reduce systemic levels of NO2-/NO3-, and further suggest that this feature of TGF-β1 can be harnessed for therapy and diagnosis of interstitial cystitis.